Determinants of green purchase intention in Nigeria: The mediating role of green perceived value - Karatu, Victoria Masi Haruna; Nik Mat, Nik Kamariah (2015)
The purpose of this paper is to examine the factors which may influence green behaviour in Nigeria.The study explores the influence of green price sensitivity, perceived behavioural control, green trust, government regulations, perceived green knowledge on green purchase intention and also the mediation effect of green perceived value between these determinants and green purchase intention.In actualizing this, quantitative survey was conducted involving 750 self administered questionnaires to university lecturers.440 datasets were usable after screening; with these the analysis was carried out using structural equation modelling (SEM).The findings unveiled that perceived green knowledge, green perceived value and perceived behavioural control have significant direct relationship with green purchase intention; perceived behavioural control, green trust, government regulations and perceived green knowledge have positive and significant relationship with perceived value.On the mediation, green perceived value mediates between perceived green knowledge, government regulation, and green trust, perceived behavioural control and green purchase intention.This paper sheds light on the consumer’s behavioural intentions towards green in the Nigerian context and will heighten the coordination of marketing strategies and government policy for environmental sustainability.